Prediction of maximal lactate steady state in runners with an incremental test on the field - Leti, T.; Mendelson, M.; Laplaud, D.; Flore, P. (Journal of Sports Sciences, 2012)
During a maximal incremental ergocycle test, the power output associated with Respiratory Exchange Ratio equal to 1.00 (RER = 1.00) predicts maximal lactate steady state (MLSS). We hypothesised that these results are transferable for runners on the field. Fourteen runners performed a maximal progressive test, to assess the speed associated with RER = 1.00, and several 30 minutes constant velocity tests to determine the speed at MLSS. We observed that the speeds at RER = 1.00, at the second ventilatory threshold (VT2) and at MLSS did not differ (15.7 ± 1.1 km/h, 16.2 ± 1.4 km/h, 15.5 ± 1.1 km/h respectively). The speed associated with RER = 1.00 was better correlated with that at MLSS (r = 0.79; p = 0.0008) than that at VT2 (r = 0.73; p = 0.002). Neither the concentration of blood lactate nor the heart rate differed between the speed at RER = 1.00 and that at MLSS from the 10th and the 30th minute of the constant velocity test. Bland and Altman analysis showed a fair agreement between the speed at MLSS and that at RER (0.2 ± 1.4 km/h). This study demonstrated that the speed associated with RER = 1.00 determined during maximal progressive track running allows a fair estimation of the speed associated with MLSS, markedly decreasing the burden of numerous invasive tests required to assess it.